Diagenetic Pattern in the Citarate Carbonate Rocks, Cilograng Area, Lebak Regency, Banten Province - Basuki, N. I.; Wiyoga, S. A. (Indonesian Journal on Geoscience, 2012)
DOI:Â 10.17014/ijog.v7i3.142The carbonate sequence overlies conformably the tuffaceous sandstone unit, and in turn is conformably underlain by the tuff-sandstone unit, both of which are members of the Citarate Formation. The Citarate carbonate rocks were deposited in an open platform back reef environment, which was temporarily drowned by local sea level rise. Regional Middle Miocene deformation formed NNE-WSW trend faults and E-W trend folds in the researched area. This paper discusses the nature of diagenetic alteration of the Citarate carbonate rocks based on petrographic analyses of twenty surface samples. Carbonate rocks from bottom to top comprise algae packstone, packstone-grainstone, coral-algae packstone, and foraminifer wackestone-packstone. Fragments of coral, coralline red algae, and large foraminifera are the dominant bioclasts in most of the observed samples, whereas echinoids and bivalves are less abundant; they are set in a recrystallized micrite matrix. Planktonic foraminifera are abundant only in few samples. Fragments of plagioclase, igneous volcanic rocks, pyroclastic rocks (tuff), and much less abundant quartz are commonly present in all the studied samples. A generalized diagenesis includes early marine cementation by fibrous aragonite, compaction, aragonite dissolution and/or neomorphism, precipitation of equant-grained calcite cement in a phreatic environment, dissolution to form moldic porosities, dolomitization, the formation of stylolites and fractures, and precipitation of late ferroan calcite during burial. Multiple carbonate cements occur as pore-filling phases, with ferroan calcite cementation taking place during later-stage burial. Secondary porosities were formed during different stages in diagenetic processes, such as dissolution, dolomitization, and stylolite and fracture formations. Although precipitation of nonferroan and ferroan calcite cement occluded porosities, porosity enhancement during early selective dolomitization might still be significant. Current observations also revealed the presence of intraparticle, micro-vuggy, and fracture porosities in different samples.